Nanotechnology Revolutionizing Heat Transfer: A Review of Nanofluid Research and Applications - Kulandaivel S.; Samykano M.; Keng N.W.; Rajamony R.K.; Suraparaju S.K.; Sofiah A.G.N.; Kalidasan B. (Malaysian Institute of Chemistry, 2025)
Nanofluids are a mixture of nanosized particles dispersed in a fluid that has gathered significant interest due to their ability to enhance thermal conduction and heat transfer processes. This comprehensive review delves into formulation methodologies, thermal and physical characteristics, and the applications of nanosuspensions in heat transfer. Various techniques are used to prepare heat transfer nanofluids with uniform dispersion and stable suspension. Common methods include mechanical stirring, sonication, chemical synthesis, and surface modification. These methods are influenced by nanomaterials' dimension, structure, and surface properties, ultimately shaping nanofluids' thermophysical characteristics. Thermophysical properties like thermal conductivity, viscosity, and heat capacity are notably improved in nanofluids compared to base fluids. However, increasing nanoparticle concentration increases the fluid viscosity, requiring careful consideration for practical applications. Heat transfer nanofluids find applications across various industries, including thermal management systems, heat exchangers, electronics cooling, and renewable energy systems. They improve the performance and efficiency of heat transfer equipment, enhance thermal conductivity in electronics cooling, and optimize energy harvesting processes in solar collectors. In conclusion, heat transfer nanofluids present promising opportunities to improve thermal conductivity and heat transfer efficiency in diverse applications. Continued research and development in formulation methods, understanding of thermophysical properties, and exploring new applications are crucial for fully realizing the potential of heat transfer nanofluids in various engineering fields. ? 2024 Malaysian Institute of Chemistry. All rights reserved.